Numerical simulation of the flow rate effect on the evolution of a negatively buoyant water jet - Allal, Abderrrahim; Khechekhouche, Abderrahmane; Driss, Zied (جامعة الوادي - university of el oued, 2020)
A numerical simulation study was done on a penetrating pure water jet injected into another surrounding salt water miscible with negative buoyancy conditions. For the incompressible filtered Navier-Stokes equations and the sum of the fluid model volume, we used a transient Computational Fluid Dynamics (CFD) solver (VOF model). A finite volume discretization method using Open Source code given in Open Foam 2.3.0. was used to solve these equations. The flow has a significant impact in the laminar system on the evolution of the jet in terms of subsequent permanent phase as well as transient regime
Article
Keywords: Pure water jet, saltwater, transient penetration, stationary profile